The Presentation-Practice Route to Teach Vocabulary to Young Learners: A Casa Study at International Schools in Uzbekistan - Rimajon Sotlikova (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Teaching vocabulary to young learners is an essential aspect of language acquisition that requires a specific approach or strategy to ensure that learners acquire a wide range of vocabulary. Expanding vocabulary is a critical aspect of language learning as it equips learners with the learning tools to confidently articulate their thoughts and ideas in the target language. Developing vocabulary also enables learners to grasp complex concepts and ideas. One technique that has proven effective in language classes is the presentation-practice route. In light of this, the purpose of this study is to describe the teaching techniques employed by English teachers at Genius International School in Tashkent, Uzbekistan, when using the presentation-practice route to teach English vocabulary. The study adopted a descriptive research methodology, with data collection conducted through interviews and observations of English teachers at the school. Qualitative analysis was used to analyze the data collected from the respondents. The study's findings revealed that the teachers employed several techniques to encourage learners' mastery of vocabulary, including contextualization, the use of visual aids, and the incorporation of interactive activities. These techniques were found to be effective in facilitating learners' comprehension and retention of English vocabulary.